Information System Application Use on Blended Learning Readiness Analysis - Indah Kartika Sandhi (Journal of Research in Business, Economics, and Education, 2021)
Changing in learning method as a Covid-19 Pandemic effect force educational institution to modified learning system. Learning activity shift from face-to-face learning to online learning. This research aims to test and analyze the influence of using information system applications on blended learning readiness. Research data were collected by distributing the questionnaire through the student. This research conducts a purposive sampling technique. Research data were tested by conducting validity test, reliability test, and regression analysis. The research’s result shows that there is a positive influence of information system application use on blended learning readiness. This research implies that using information systems application help student in accomplishing study by online learning. The readiness of student and institution needed to the successful of blended learning implementation. Future research should consider the student attitude as well as lecturer capabilities in blended learning. Keywords: Information System Applications Use, Blended Learning Readiness, Covid-19 Pandemic.